The impact of software process consistency on residual defects. Issue 9 (22nd May 2015) - Huang, Fuqun; Liu, Bin; Wang, Shihai; Li, Qiuying
Abstract: Residual defects at the time of delivery are an important concern for safety critical software systems. Suppliers and customers are urged to get evidence for what they can do to reduce residual defects. Thus, it is meaningful to learn from historical data concerning the kinds of defects that have escaped from the existing quality assurance approaches and the factors that lead to the residual defects. A total of 3747 defects from 70 software systems developed by 29 Chinese aviation organizations were collected from acceptance tests during the last 5 years. For all these organizations, 38 domain experts from the industry assessed the process consistency to the standard built in the framework of Capability Maturity Model (CMM). Results demonstrate that the process improvement in the range of high consistency is effective in reducing total defects, as well as the minor and severe defects. The high consistency adoption of the practices in CMM Level 1 to Level 3 is more effective in reducing minor defects than severe defects. Causal analysis was performed to investigate the underlying mechanisms. Results reveal that individual cognitive failures cause 87% of severe defects. More approaches to help software developers manage their interior cognitive process are needed for improving software quality in the future. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Process improvement in the range of high consistency is effective in reducing both of the severe and total residual defects. However, in the range of low consistency, process improvement is found to be negatively related to reducing residual defects. Software verification is found to be the most effective among all the key process areas. Approaches to help software developers manage their interior cognitive process are needed, as severe residual defects are mainly due to individual cognitive failures.